d. -9x-6x=x(-9-6)=x(-15)=-15x
pour exercice6:f =42-14x=14 (3-x)
pour exercice 1o:5x+3x=x (5+3)=8x
le reste est bon
Quest18:

-256 +1
+16 -16 -1 -1
-4 -4 +4 -1 +1 -1
-2 +2 -2 -2 -1 +1 +1 -1

Réponses

2013-12-26T22:32:43+01:00
18
Rose :
Colonne 3 gauche droite : 0 0 4
Colonne 2 gauche droite : 0 4
Colonne 1 gauche droite : 4

Bleu :
Colonne 3 g- d : 0 2 0
Colonne 2 g-d : 2 2
Colonne 1 : 4

6 :
A = 16x + 4
A = 4* (4x + 1)

B=9-72x
B= 9* (1-9x)

C= 12-8x
C= 4* (3-2x)

D= -6x-18
D= 6* (x-3)

E=9x+ 6
E= 3* (3x+ 2)

F=42-14x
F= 2*(21-7x)

10 :
A. 5x + 3x
= x +8
= 8x

B. 3x - 8x
= x-5

C. -4x + 15x
= x + 11
= 11x

D = -9x -6x
= x- 15